Functional and Cognitive Impairments Increased Risks of Outcomes of Healthcare Utilization in Patients With Stroke Receiving Home and Community-Based Care in Taiwan - Liu, Li-Fan; Wang, Wei-Ming; Wang, Jung-Der (Frontiers in Public Health, 2021)
Aim: Stroke is a leading cause for disability, however, little has been known about the utilization outcomes of LTC recipients in Taiwan. This study aimed to quantify the disease burdens of stroke survivors receiving LTC by evaluating their utilization outcomes including mortality, readmissions and re-emergency within one year after stroke diagnoses. Methods: By interlinkages among the national mortality registry, LTC dataset and the National Health Insurance Research Dataset (NHIRD), the outcomes and the factors associated with receiving LTC up to one year were explored. Patients were aged 50 years and over with an inpatient claim of first diagnosis of Stroke of intracerebral hemorrhage and ischemic stroke during 2011-2016. Health care utilization outcomes including rehospitalizations and re-emergency. Results: There were 15662 stroke patients who utilized the LTC services in the dataset among the stroke population in NHIRD. Stroke survivors receiving LTC showed no difference in clinical characteristics and their expected years of life loss (EYLL=7.4 years) among those encountered in NHIRD. The LTC recipients showed high possibilities to be re-hospitalized and re-sent to emergency service within one-year after diagnosis. Apart from the comorbidity and stroke severity, both the physical and mental functional disabilities as well as caregiving resources predicted the utilization outcomes. Conclusions: For stroke survivors, both severe functional impairments and cognitive impairments were found as important factors for health care utilizations. These results regarding reserving functional abilities deserve our consideration in making decision of ongoing LTC policy reform in the aged society of Taiwan.